Customer Orientation and Leadership in the Health Service Sector: The Role of Workplace Social Support - Bruno, Andreina; Dell’Aversana, Giuseppina; Zunino, Anna (Frontiers in Psychology, 2017)
Health care is a critical context due to unpredictable situations, demanding clients, workload, and intrinsic organizational complexity. One key to improve the quality of health services is connected to the shift in organization perspective of viewing patients as active consumers rather than passive users. Therefore, higher levels of customer orientation (CO) are expected to improve organizational service effectiveness. According to a cultural perspective to CO, the aim of the study was to explore how different leaders’ behaviors (task-oriented and relationship-oriented) interact with CO of health organizations. Specifically, the aim of the paper was to contribute to this topic, by considering the leaders’ point of view. Since leader’s experience of CO is influenced by social processes in the work environment, workplace social support (WSS) was inserted as moderator in the relationship between leader behavior and CO. A survey study was conducted among 57 Health Department directors belonging to the National Health Service in the North of Italy in 2016. Findings showed that WSS moderated the influence of leadership concern for relationship on CO. Practical implications of the study are discussed.